Frontispiece: Nanoparticle@Metal‐Organic Frameworks as a Template for Hierarchical Porous Carbon Sponges. Issue 51 (12th September 2018) - Salazar‐Beltrán, Daniel; Cabello, Carlos Palomino; Guzmán‐Mar, Jorge Luis; Hinojosa‐Reyes, Laura; Palomino, Gemma Turnes; Maya, Fernando
Abstract : Hierarchically porous carbon sponges (HCS) have been prepared from ZnO@ZIF‐8 porous crystal precursors. HCS have been implemented in membrane format for the fast and efficient extraction of toxic phthalate esters from water. For more details, see the Full Paper by J. L. Guzmán‐Mar, F. Maya et al. onpage 13450 ff.